Analisis Prediksi Kebangkrutan Menggunakan Metode Altman (Z-Score) Pada Perusahaan Farmasi (Studi Kasus Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2011 – 2015) - fitria wulandari; Burhanudin Burhanudin; Rochmi Widayanti (Benefit: Jurnal Manajemen dan Bisnis, 2017)
This study aimed to analyze the condition of the company using the Altman Z-Score to predict the potential bankruptcy of the five pharmaceutical companies listed on the Indonesia Stock Exchange in 2011 to 2015. The sampling method  is using purposive sampling with a sample of five pharmaceutical companies. This research is descriptive with quantitative approach. The results showed that: (1)  in 2011 to 2015 the five pharmaceutical companies are in the good category, the number of  Z-Score from all companies are  ≥ 2.99. (2) Moreover  from the five pharmaceutical companies that were analyzed PT Merck Tbk in 2011, 2013 and 2014 had the highest number for Z-Score at 8.45, 6.3 and 5.92. (3) PT Kalbe Farma Tbk in 2012 and 2014 had the highest number for Z Score at 6.08 and 5.91. The results of this study are expected for pharmaceutical companies to maintain liquidity to meet all its obligations so that will interest   investors and creditors. Companies are expected  to manage assets to increase sales and generate profits.